The role of traditional Chinese medicine in modulating gut microbiota to alleviating insulin resistance in polycystic ovary syndrome - Yin, Lin; Yang, Wanqiu; Xie, Qingling; Xu, Jili; Lan, Ying; Wu, Jie (Frontiers in Nutrition, 2025)
Polycystic ovary syndrome (PCOS) is a common endocrine and metabolic disorder characterized by hyperandrogenism, anovulation, and insulin resistance (IR). Recent evidence suggests that gut microbiota (GM) dysbiosis contributes to PCOS pathophysiology, connecting metabolic, immune, and hormonal disturbances. Reduced microbial diversity, depletion of short-chain fatty acid (SCFA)-producing bacteria, and enrichment of endotoxin-producing taxa disrupt intestinal barrier integrity, promote low-grade inflammation, and aggravate IR, thereby fueling a vicious cycle of hyperinsulinemia and hyperandrogenism. Traditional Chinese medicine (TCM) has shown unique advantages in modulating GM and alleviating PCOS-IR. Herbal formulas, active compounds (e.g., berberine), acupuncture, and dietary therapies such as inulin, quinoa, and flaxseed oil restore microbial balance, enhance SCFA production, regulate bile acid metabolism, and strengthen gut barrier function. These effects mitigate endotoxemia, suppress chronic inflammation, and improve insulin sensitivity. This review summarizes advances in understanding the role of GM in PCOS-IR and emphasizes TCM as a promising microbiota-targeted therapeutic approach.